Effect of a potential probiotics Lactococcus garvieae B301 on the growth performance, immune parameters and caecum microflora of broiler chickens. Issue 3 (30th August 2015) - Zhang, T.; Xie, J.; Zhang, M.; Fu, N.; Zhang, Y.
Summary: In this study, a novel Lactococcus garvieae B301 was isolated from the intestinal tract of a healthy piglet. L. garvieae B301 was tolerant to acid pH, simulated gastric and small intestinal transit juices, indicating that it was capable of surviving in the gastrointestinal tract. L. garvieae B301 was safe and beneficial to broilers, as broiler chickens supplemented with L. garvieae B301 had lower diarrhoea incidence and mortality than the Control. Moreover, supplementation of broiler diets with L. garvieae B301 resulted in an increase in body weight and the number of caecum lactic acid bacteria and Bifidobacterium spp., and decrease in feed‐to‐gain ratio and the number of caecum coliforms. It also had a positive effect on the thymus index and bursa of Fabricius index and enhanced serum levels of immune globulins. All these results showed that L. garvieae B301 could enhance the growth performance of broiler chickens and improve their health. Thus, L. garvieae B301 could be a promising feed additive for broiler chickens.